Metric tensors for homogeneous, isotropic, 5-dimensional pseudo riemannian models (1998)
In this paper westudy the metric tensor of a homogeneous, isotropic, 5-dimensional pseudo Riemannian space, solving the corresponding Einstein equations when the spatial component is flat, spherical or pseudo spherical